Synergetic effects of short carbon/basalt hybrid fibers on the mechanical, thermal and nuclear shielding properties of DCBA/BA-a resin composites. (October 2019) - Zegaoui, Abdeldjalil; Derradji, Mehdi; Ghouti, Hamid Abdelhafid; Medjahed, Aboubakr; Zu, Li-wu; Liu, Wen-bin; Wang, Jun; Dayo, Abdul Qadeer; Liu, Yu-guang
Abstract: This manuscript aimed to examine the impact of the hybridization process of hybrid fibers consisting of carbon and basalt fibers on the properties of thermosetting resin blends composed of dicyanate ester of bisphenol-A (DCBA) and bisphenol-A based benzoxazine (BA-a) resins. According to data gathered, the mechanical properties of the hybrid fibers reinforced the DCBA/BA-a blend composites were chiefly improved when compared to the base samples' properties, while the hybridized composites showed much enhanced thermal stability degradation at higher temperatures. The shielding evaluations disclosed that the integration of the hybrid fibers helped the DCBA/BA-a blend to possess excellent nuclear shielding properties. With respect to the properties of the as-used reinforcing systems, performing the structural and morphological analyses permitted us to prove that the enhanced quality of the reinforcing agents inside the thermoset resin blend was possibly behind these ameliorations in the investigated performances. Highlights: Novel carbon/basalt fibers reinforced blend based hybrid composites with enhanced properties were successfully prepared. Maximum flexural strength and modulus were observed after hybridization of 15 wt% carbon fibers and 15 wt% basalt fibers. The hybrid fibers filled blend composites showed excellent thermal resistances at higher temperatures. The prepared hybrid composites revealed outstanding gamma-radiation shielding properties.